Longitudinal study of Good Pharmacy Practice roles covered at the annual world pharmacy congresses 2003-2019 - Zuzana Kusynová; Hendrika A. van den Ham; Hubert G. M. Leufkens; Aukje K. Mantel-Teeuwisse (Taylor & Francis Group, 2022)
Background Globally accepted roles of pharmacists are described in the Good Pharmacy Practice (GPP) standards, published by the World Health Organization (WHO) and the International Pharmaceutical Federation (FIP) in 2011. These standards provide a wide-ranging description of four main roles pharmacists fulfil. The global platform, where pertinent discussions around excellence and innovation in various pharmacy roles take place, is the annual congress of the pharmacy organisation representing the profession globally, FIP. Objectives Given the world pharmacy congresses present and reflect on the most topical and contemporary matters, this longitudinal study aimed at creating a historical overview of the frequency of appearance of the different GPP roles in the programmes of the past 17 congresses (2003-2019). This is to distinguish the dominance of different roles over time and thus their relevance for the profession. Methods The GPP standards served as a framework to create a set of keywords that were analysed for their frequencies of appearance in the programmes through text analysis. Trends in the four overarching GPP roles and at individual keyword level were analysed descriptively over time. Results The study found that all four GPP roles appeared in the programme each year and none of them was significantly missing, neither in the decade preceding the publication of the GPP standards nor in the decade thereafter. Role 3 "Maintain and improve professional performance" was most frequently represented, also demonstrating an upward trend in appearance, together with Role 4: "Contribute to improve effectiveness of the health-care system and public health". Trends emerged towards patient-centred clinical focus and positioning pharmacy as an important player in the health-care system-observed also at individual keywords level in areas such as health promotion-away from the more traditional product-centred practice roles such as compounding. Conclusions GPP roles have been already covered by the FIP annual congresses (long) before 2011, when the GPP roles were formally adopted, and they stayed relevant in the decade after. The more pronounced dominance toward the roles related to improving professional performance and positioning pharmacy are in line with the trend that the rather technical topics in pharmacy are increasingly covered by specialised meetings and that the FIP annual congresses have moved toward more general, scholarly platforms for dialogue and conversation.